Fred Rogers and children's spirituality: valuing the uniqueness of others and caring for others. Issue 2 (3rd April 2019) - Harris, Kathleen I.
ABSTRACT: Mister Rogers' Neighborhood   was a safe haven advocating kindness, empathy, and caring for all children.  Making everyone feel loved, Fred Rogers captured the attention and curiosity of young children across America with his compassionate manner, intentional listening skills, and respect for all individuals by encouraging children to feel good about themselves.  This article explores the ministry of Fred Rogers and how his approach to children's spirituality focused on valuing the uniqueness of each individual, human connections through play, and caring for others by recognizing spiritual moments and teaching the whole child while appreciating the uniqueness of others.  His genuine and patient presence had a healing quality, creating a world for children in which real learning and unconditional love could flourish.  The messages of tolerance and acceptance by recognizing and respecting other's beliefs, and unconditional love and care, were beacons of hope for all.